The Role of Facility Design in Preventing Healthcare-Associated Infection: Interventions, Conclusions, and Research Needs. (October 2013) - Zimring, Craig; Denham, Megan E.; Jacob, Jesse T.; Kamerow, Douglas B.; Lenfestey, Nancy; Hall, Kendall K.; Kasali, Altug; Cowan, David Z.; Steinberg, James P.
OBJECTIVE: To summarize the findings and provide recommendations based on the multidisciplinary literature review and industry scan, focusing on the links between the built environment and healthcare-associated infections. To propose a research agenda in order to increase informed design decisions and advance the evidence base. BACKGROUND: The HAI-Design project explores the research linking a range of design interventions to healthcare-associated infection. The multidisciplinary team evaluated over 3, 800 articles and conducted interviews with a range of stakeholders including CEOs, architects, designers, physicians and other healthcare experts, the results of which are featured in this special Supplement as topical papers. TOPICAL HEADINGS: The four topical papers describing the role of the built environment in the acquisition of healthcare-associated infections are summarized. The evidence evaluating the strategies for intervention through the built environment is analyzed, and a research agenda is proposed. CONCLUSIONS: While the evidence base supporting the efficacy of strategies and technologies continues to grow, there are currently few data that demonstrate a reduction in infection rates. The need for multidisciplinary collaboration and increased efforts to standardize the evaluation of environmental studies are essential to overcome the many challenges and improve the reliability of data